Toward an Improved Haptic Zooming Algorithm for Graphical Information Accessed by Individuals who are Blind and Visually Impaired. - Rastogi, Ravi; Pawluk, Dianne T. V. (Assistive Technology, 2013)
An increasing amount of information content used in school, work, and everyday living is presented in graphical form. Unfortunately, it is difficult for people who are blind or visually impaired to access this information, especially when many diagrams are needed. One problem is that details, even in relatively simple visual diagrams, can be very difficult to perceive using touch. With manually created tactile diagrams, these details are often presented in separate diagrams which must be selected from among others. Being able to actively zoom in on an area of a single diagram so that the details can be presented at a reasonable size for exploration purposes seems a simpler approach for the user. However, directly using visual zooming methods have some limitations when used haptically. Therefore, a new zooming method is proposed to avoid these pitfalls. A preliminary experiment was performed to examine the usefulness of the algorithm compared to not using zooming. The results showed that the number of correct responses improved with the developed zooming algorithm and participants found it to be more usable than not using zooming for exploration of a floor map.